(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study explores how individuals interpret online love fraud experiences and how these experiences reshape trust, meaning, and social interactions in digital spaces as part of a society’s socio-cultural resilience. Study Design/Methodology/Approach: A qualitative phenomenological approach through Interpretative Phenomenological Analysis with in-depth interviews was used in this study to understand subjective meaning formation, emotional interpretations, and relational negotiations in online love fraud experiences. Findings: Digital love fraud develops through gradual relational constructions that shape emotional intimacy and symbolic trust, which are interpreted as disruptions to the sense of security and relational valuations and influence people’s social interaction patterns in the digital world, thus impacting sociocultural resilience. Originality/Value: This research positions the lived experiences of victims as the analytical basis for understanding relational vulnerability in the digital space and demonstrates its connection to the formation of socio-cultural resilience in contemporary Indonesian society.